Revisiting non-chemical modes of diseases and pests management in tea (Camellia sinensis): A review - BORA, POPY; BORA, L C (The Indian Journal of Agricultural Sciences, 2022)
Tea [Camellia sinensis (L) O. Kuntze] like any other perennial plantation crop is subjected to loss in biomass yield and functional quality, once exposed to beyond economic thresholds of diseases and pests load. A battery of diseases and pests are reported to badly affect the tea industry of India. Microbial antagonists and botanicals emerged as two most vibrant via-media of addressing tea diseases and pests amongst non-chemical modes, in a manner, closest to residue free production system. Authors revisited the use of microbial antagonists and botanicals through comprehensive updated analysis of breakthroughs recorded in the success of microbial antagonists-and botanicals mediated diseases and pests management in tea. Our efforts also portrays the futuristic viewpoints in terms of developments of commercial formulations of botanicals using their bioactive compounds, consortium of bioagents and fortification of botanicals with bioagents through area wide field response studies in the back drop of growing demand of organic tea, the most pressing developmental issue of tea industry.